Advanced Pre-fetching Based Dynamic Data Replication under Small World Network Model - Singh, Rekh Nath; Singh, Raghuraj (International Journal of Integrated Engineering, 2019)
The database replication keeps up contents of database such as tables, in various geographical locations that fabricate an arrangement of distributed database. The necessities of database replication are expanding with the time as the use of internet is also increasing. With the purpose of meeting these prerequisites, priorities among requests can be included. In this work two types of priorities i.e., low and high priority is considered in this research article. It is noticeable that the high priority requests are more vital in comparison to low priority requests and therefore low priority requests can be delayed or dropped. The rate of request loss can be lessened utilizing the conditions of load balancing where a portion of the contending requests are transferred to other nodes. In this paper, internet is modelled as small world network, and performance assessment of A-PDDRA (Advanced Pre-bringing Based Dynamic Data Replication Algorithm) is carried out on small world network while considering both priorities and load balancing using computer simulation.